Analisis Kualitas Website SIPD Penajam Paser Utara Menggunakan Webqual 4.0 - Dewi; Erlin Setyaningsih (LPPM Universitas Mulia, 2022)
This study aims to determine the quality of using the SIPD website used by civil servants in North Penajam Paser with the address https://sipd.kemendagri.co.id as a system for documenting, managing, and transforming regional development data into information that is presented to the public and as a decision-making document in the context of planning, implementing, and evaluating local government performance. The categories used in this study were usability quality, information quality and interaction quality. Material collection using a questionnaire with 22 statements from 3534 people from the population of civil servants in North Penajam Paser in 2020 based on data from the regional civil service agency of East Kalimantan province. The sample was calculated using the Slovin formula with an error rate of 10%, totaling 98 people. The steps to analyze the quality of the website by describing the data from the questionnaire and testing the data are validity and reliability tests. In addition, data analysis was performed by calculating th score and averages for each indicator. The calculation results show that the average usability quality category is 4.63, the information quality is 4.66 and the interaction quality is 4.66 so that the SIPD Penajam Paser Utara website is of very high quality.